Correction: Robust liquid-repellent coatings based on polymer nanoparticles with excellent self-cleaning and antibacterial performances. Issue 3 (4th January 2017) - Fu, Yuchen; Jiang, Jingxian; Zhang, Qinghua; Zhan, Xiaoli; Chen, Fengqiu
Abstract : Correction for 'Robust liquid-repellent coatings based on polymer nanoparticles with excellent self-cleaning and antibacterial performances' by Yuchen Fu et al., J. Mater. Chem. A, 2017, 5, 275–284.